2014
DOI: 10.1021/nl403979s
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Germanium Nanowire-Based Lithium-Ion Battery Anodes Extending over 1000 Cycles Through in Situ Formation of a Continuous Porous Network

Abstract: Type of publicationArticle ( Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
340
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 331 publications
(366 citation statements)
references
References 43 publications
22
340
1
3
Order By: Relevance
“…[42] In the interim, the same phenomenon has been reported for Sb, Si, and Ge anodes. [35,43,44] This occurrence was also noted by Li et al, where a large amount of fusion between Si NWs was observed at both fully lithiated and delithiated states. [43] The mechanism of fusion is electrochemically initiated during charging as Li atoms can simultaneously bond at the point of contact between two adjacent NWs creating an M-Li-M bridge (Figure 3b).…”
Section: Lithium-assisted Weldingsupporting
confidence: 60%
See 2 more Smart Citations
“…[42] In the interim, the same phenomenon has been reported for Sb, Si, and Ge anodes. [35,43,44] This occurrence was also noted by Li et al, where a large amount of fusion between Si NWs was observed at both fully lithiated and delithiated states. [43] The mechanism of fusion is electrochemically initiated during charging as Li atoms can simultaneously bond at the point of contact between two adjacent NWs creating an M-Li-M bridge (Figure 3b).…”
Section: Lithium-assisted Weldingsupporting
confidence: 60%
“…In a recent study by our group on Ge NW anodes, it was shown that the addition of as little as 3 wt% VC to a 1 M LiPF 6 ethylene carbonate/dimethyl carbonate electrolyte can significantly improve the performance, with the electrode retaining 80% of its initial capacity after 200 cycles, compared to only 58% when using an additive-free electrolyte. [35] Similar improvements in the performance of Si NW electrodes through the use of electrolyte additives have also been reported. [36] The majority of these studies have focused on using additives that have previously shown promise in improving the performance of graphitic-based electrodes.…”
Section: Research Newssupporting
confidence: 59%
See 1 more Smart Citation
“…37 The capacities values obtained over 15 cycles were greater than previously reported values for Au-seeded Ge nanowires 36,42 and comparable to values reported for Ge nanowires catalyszd with Sn , and like In, it also reversibly alloys with Li. 6 Previous reports indicate that Au does not reversibly alloy with lithium causing Au-seeded Ge nanowires to suffer from significant capacity fading issues. 17 In has previously been shown to …”
Section: Electrochemical Experiments Of Ge Nanowires Synthesised Withmentioning
confidence: 99%
“…Electrochemical reactions were previously demonstrated effectively in fabricating meso-and nanoporous structures with well-controlled pore structure and chemical compositions, greatly improving the performance of electrode materials 25 . Different mechanisms were proposed for the formation of porous structures, for example, by galvanic replacement reactions 26 due to different reduction potentials or through a nanoscale Kirkendall effect due to different diffusion rates of migrating species [27][28][29] .…”
mentioning
confidence: 99%